2013
DOI: 10.1063/1.4792202
|View full text |Cite
|
Sign up to set email alerts
|

Thermostats and thermostat strategies for molecular dynamics simulations of nanofluidics

Abstract: The thermostats in molecular dynamics (MD) simulations of highly confined channel flow may have significant influences on the fidelity of transport phenomena. In this study, we exploit non-equilibrium MD simulations to generate Couette flows with different combinations of thermostat algorithms and strategies. We provide a comprehensive analysis on the effectiveness of three thermostat algorithms Nosé-Hoover chain (NHC), Langevin (LGV) and dissipative particle dynamics (DPD) when applied in three thermostat str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 65 publications
2
80
0
Order By: Relevance
“…keeping the walls rigid), has a significant effect on properties of fluids undergoing Couette flow [31]. Yong and Zhang [32] 5 extended this work, comparing the effects of LGV, dissipative particle dynamics (DPD) and simulations with NH chain thermostats on Couette flow of Lennard-Jones particles, thermostatting walls and/or fluid and found that thermostatting the walls gave better agreement with experiments. A recent work on the diffusion rates of water through carbon nanotubes subject to pressure gradients showed discrepancies in the results obtained using different thermostatting methods [33].…”
Section: Introductionmentioning
confidence: 99%
“…keeping the walls rigid), has a significant effect on properties of fluids undergoing Couette flow [31]. Yong and Zhang [32] 5 extended this work, comparing the effects of LGV, dissipative particle dynamics (DPD) and simulations with NH chain thermostats on Couette flow of Lennard-Jones particles, thermostatting walls and/or fluid and found that thermostatting the walls gave better agreement with experiments. A recent work on the diffusion rates of water through carbon nanotubes subject to pressure gradients showed discrepancies in the results obtained using different thermostatting methods [33].…”
Section: Introductionmentioning
confidence: 99%
“…For confined NEMD simulations, alternative thermostatting strategies are required; Yong and Zhang [54] evaluated some of these in 2013. In confined NEMD simulations, the thermostat is usually only applied to the wall atoms [54], allowing a thermal gradient to develop through the thickness of the lubricant film, as occurs in real experiments [55].…”
Section: Temperature and Pressure Controlmentioning
confidence: 99%
“…In confined NEMD simulations, the thermostat is usually only applied to the wall atoms [54], allowing a thermal gradient to develop through the thickness of the lubricant film, as occurs in real experiments [55]. The 6 Friction | https://mc03.manuscriptcentral.com/friction localised thermostat is often only applied in the Cartesian directions perpendicular to the shearing direction in order to avoid significantly affecting the dynamics.…”
Section: Temperature and Pressure Controlmentioning
confidence: 99%
“…[51][52][53] Thermostatting the wall atoms rather than the confined sample is the most physically realistic option. The implementation of bulk system thermostats without modification may lead to spurious particle dynamics.…”
Section: Thermostattingmentioning
confidence: 99%